El clima laboral y el desempeño del personal en la cooperativa de transporte en taxis Auca Libre, provincia de Orellana. - Gonzaga Maza, Cristian Ariel (2023)
This thesis focuses on determining how the work environment affects the performance of the Auca Libre taxi transport cooperative staff in the province of Orellana. It is proposed that the work environment is a key factor for the success of any company, as it directly affects productivity, profitability, and staff performance. The aim is to analyze, diagnose and create a model for improving the working environment to promote the efficient performance of staff and the achievement of the competitive goals set by the company. The methodology used is a non-experimental design (documentary-field and descriptive), and data collection techniques are used through a population of 101 partners for subsequent statistical processing. It is concluded that the organizational climate is vital in promoting ideal conditions for carrying out work activities in the cooperative, which could contribute to improving the work performance of the staff and the achievement of the objectives proposed by the organization.